Communicating bad news - Paes da Silva, Maria Júlia (O Mundo da Saúde, 2012)
This paper presents a review on the theme “communicating bad news”, discussing the possible reason health care professionals have difficulties to talk about the terminally sick patient process and showing factors able to make this moment more bearable and hospitable. It presents proposals for action in the verbal and nonverbal dimensions of interpersonal communication aiming to reduce stress and anxiety affecting patients, their families and professionals.